HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT PRENATAL DISTRESS PADA IBU HAMIL PRIMIGRAVIDA - Ilmi, Maulidatul; Jupriyono, Jupriyono; Aryani, Hening Ryan (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2025)
Primigravida pregnant women are very vulnerable to psychological disorders. Pregnant women who do not get support from their husbands may experience distress during pregnancy. Psychological problems in pregnancy can affect the welfare of the fetus in the womb by increasing the risk of its growth and development so that it is born with low birth weight and disability. This study aims to determine the relationship between husband support and the level of prenatal distress in primigravida pregnant women. The research design used correlation analytics with a cross-sectional approach. The population was all primigravida pregnant women at TPMB Siti Rugayah Pakis District who were recorded in the cohort register from July 2023-May 2024 with a total sampling technique of 28 respondents. The instrument used husband support questionnaire and NuPDQ. Data were analyzed using the Spearman test with an error rate (? = 0.05). Most of the respondents' husbands were in the supportive category (59.4%) and almost half of the respondents had mild prenatal distress levels as many as 12 respondents (37.5%). Spearman test results showed no significant relationship between husband support and the level of prenatal distress in primigravida pregnant women (p value>0.05). There is no significant relationship between husband support and the level of prenatal distress in primigravida pregnant women. Pregnant women who get support from their husbands have a tendency to experience mild prenatal distress. Promotive efforts to minimize the level of prenatal distress are by carrying out anxiety screening in pregnant women using pregnant women's monitoring sheets in the MCH book and launching a pregnant women's class program that is at least once attended by husbands to increase husband's support for his wife's pregnancy